Exploring the nucleus accumbens circuit and oxytocin therapy in a Sapap3 knockout mouse model of trichotillomania - Yuan Wang; Jingjing Yu; Rui Ma; Yundong Chen; Shihao Lu; Jianqun Fang (Scientific Reports)
Abstract Trichotillomania (TTM), an understudied psychiatric disorder, was investigated using Sapap3 knockout (KO) mice to elucidate nucleus accumbens (NAc) circuit dysfunction and oxytocin’s therapeutic potential. Under aversive conditions, KO mice exhibited TTM-like behavioral phenotypes compared to wild-type (WT) controls: elevated anxiety-like behavior (reduced total distance 33328.45 ± 6703.97 mm vs. WT 47787.22 ± 12221.33 mm; decreased standing episodes 34.20 ± 19.41 vs. WT 58.10 ± 15.55; increased immobility duration 175.05 ± 54.46 s vs. WT 90.23 ± 70.22 s, all p < 0.05), excessive grooming duration (467.43 ± 94.98 s vs. WT 391.62 ± 86.44 s, p < 0.05), and impaired social interaction characterized by elevated aggression (70 ± 10% victory rate in tube-dominance test vs. WT, p < 0.05). Calcium imaging revealed NAc neuronal hypoactivity (peak ΔF/F 0 : 2.44 ± 1.67% vs. WT 6.92 ± 2.08%, p < 0.05). Molecular analyses revealed: (1) Dopaminergic signaling alterations (increased dopamine: 26.95 ± 2.04 pg/mL vs. WT 22.43 ± 1.85 pg/mL, p < 0.05; D1 receptor up-regulation 1.29-fold and D2 down-regulation 0.89-fold). (2) Synaptic plasticity disruptions (CREB overexpression: 1.71-fold, p < 0.01; SHANK upregulation: 1.18-fold, p < 0.05). (3) SAPAP3-SHANK3 interaction deficits confirmed by immunofluorescence (compensatory SHANK3 up-regulation 1.46-fold). Oxytocin effects were paradoxical: acute administration exacerbated total grooming duration (550.45 ± 33.65 s vs. KO baseline 467.43 ± 94.98 s, p < 0.05) but reduced grooming bouts (50.80 ± 28.20 vs. 95.30 ± 31.92, p < 0.01) and attenuated aggression (victory rate against WT decreased to 65 ± 5%). Sex-stratified analysis revealed enhanced grooming severity in female KO mice (the grooming duration 526.59 ± 25.69 s vs. male KO 408.26 ± 104.33 s, p < 0.05). These findings highlight NAc circuit dysfunction and complex oxytocin effects in TTM, suggesting therapeutic targets while emphasizing the need for sex-stratified.